On The Issue Of Stem Inter-relations In Svanetian And Mengrelian-lazi Speeches - Sherozia, Revaz (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
The article deals with the issue of stems of Kartvelien languages on the data of Svanetian-Mengrelian-Lazi speeches. It offers the analyses of mistakes made while etymological researches.